Linked color imaging versus white light imaging colonoscopy for colorectal adenoma detection: A randomized controlled trial. Issue 10 (20th May 2021) - Miyaguchi, Kazuya; Takabayashi, Kaoru; Saito, Daisuke; Tsuzuki, Yoshikazu; Hirooka, Nobutaka; Hosoe, Naoki; Ohgo, Hideki; Ashitani, Keigo; Soma, Hiromitsu; Miyanaga, Ryoichi; Kimura, Kayoko; Tokunaga, Sotaro; et al.
Abstract: Background and Aim: The adenoma detection rate is an important indicator of colonoscopy quality and colorectal cancer incidence. We compared the adenoma detection rates between white light imaging (WLI) and linked color imaging (LCI) colonoscopy. Methods: Patients undergoing colonoscopy for positive fecal immunochemical tests, follow‐up of colon polyps, and abdominal symptoms at three institutions were randomly assigned to the LCI or WLI groups. Mean adenoma number per patient (including based on endoscopists' experience), adenoma detection rate, cecal intubation time, withdrawal time, mean adenoma number per location, and adenoma size were compared. Results: The LCI and WLI groups comprised 494 and 501 patients, respectively. No significant differences in the cecal intubation rate (LCI vs WLI: 99.5% vs 99.4%), cecal intubation time, and withdrawal time were noted between groups. The mean adenoma number per patient was significantly higher in the LCI group than in the WLI group (1.07 vs 0.88, P  = 0.04), particularly in the descending [0.12 (58/494) vs 0.07 (35/501), P  = 0.01] and sigmoid colon [0.41 (201/494) vs 0.30 (149/501), P  ≤ 0.001]. However, the adenoma detection rate was 47.1% in the LCI group and 46.9% in the WLI group, with no significant difference ( P  = 0.93). The total number of sessile‐type adenomas was significantly higher in the LCI group than in the WLI group (346/494 vs 278/501, P  = 0.04). As for polyp size, small polyps (≤ 5 mm) were detected at a significantly higher rate in the LCI group (271/494 vs 336/501, P  = 0.04). Conclusion: Linked color imaging is significantly superior to WLI in terms of mean adenoma number per patient.